Dynamics of Islamic Educational Institutions In Indonesia: Boarding Schools and Madrasah - Noor Rani, Ahmad; Ardiansyah, Ardiansyah; Nurhakim, Nurhakim; Faridi, Faridi (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2023)
which are the center of Islamic education activities to the many developing formal and non-formal educational institutions, including Boarding School and madrasas. Therefore, this study aims to determine the development of Islamic educational institutions in Indonesia, the Types of Islamic Education Institutions in Indonesia, the role of Islamic Education Institutions in Islamic boarding schools and madrasas in Indonesia, and the differences between Islamic boarding schools and madrasas. The research method used is literature with documentation data collection techniques. The results of this study show that Islamic boarding schools are the oldest Islamic educational institutions in Indonesia which traditional Muslims initially founded. The establishment of Madrasah in Indonesia was driven by two factors: the strengthening of the Islamic renewal movement in Indonesia and the response of Islamic education to the Dutch East Indies' educational policies. Even though they are both Islamic Education Institutions, there are many differences between Boarding School and madrasas, including Boarding School not using a curriculum, madrasah using a curriculum, and so on.